Makna Sabar dalam Tafsir An-Nur - Mulya, Prana; At Thoriq, Ibnu Nurjiin Brury; Murdianto (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2024)
Patience is the inner human attitude in retraining and desires of all needs. The strength of faith and aqidah under Islamic law can affect patients. The ability to be patient by controling lust will be glorified by Islam. An attitude of patience can makes humans refrain from degrading human dignity. Therefore, the concept of patience in the Al-Quran is human self contol based on Islamic aqidah in the guidance of the Al-Quran. In the Tafsir An-Nur written by Muhammad Hasbi, many verses explain patience, not just patience in obeying Allah and avoiding His prohibitions, but also patience in entering the field of da'wah and facing obstacles and thorns in taking this path. Patience is a very important thing when preaching, as the author was patient in preaching until he went to prison, so a preacher needs to understand the verses about patience and practice them in everyday life. The verses that the author chose and found in An-Nur's interpretation are patience regarding disasters, patience is the key to victory, patience is the nature of the prophets, and patience is the key to help. Related to patience in aspects of life that can be found are patience in obedience, patience in preaching, patience in avoiding immorality, and patience in accepting God's destiny. To seek understanding and practice interpretation of patience from Quran author choice this theme.